(untitled) (Research, Society and Development, 2021)
In this study, we discuss the possibilities of dialogicity as an epistemological political pedagogical element in order to think about the development of both critical and human senses. We understand that, by providing reflective moments, the teacher can broaden the perspectives of teaching and learning, making it possible for the subject to take hold of tools to reveal possibilities of acting in the world. Thus, we start from the following guiding question: What is the role of dialogicity as an epistemological political pedagogical element in teaching and in students’ learning? Also, from the secondary questions: How can we think of it as an educational practice for the development of critical sense and for human improvement? And how do students think of dialogicity in learning? This paper is the result of reflections arising from an activity we proposed with the topic Psychologizing: culture and its interfaces from photography, carried out in the following courses: Psychology, Human Resources, Marketing and Systems Development Analysis. We highlight that this study focuses on the experience that this activity provided to students, bringing the perceptions of the ones in the first semester of the Psychology course, in a private Higher Education institution located in Maracanaú town, in the state of Ceará, throughout the semester 2019.2. We understand that this activity allowed us to reflect on the teaching-learning process in order to realize its importance and perspectives, from the students’ praxis and view, problematizing the dialogicity in educational practice and its contributions to the education of students.